Implementıng Peer Feedback In Increasing Motivation In Speaking English Using Tiktok - Sasmi, Nafa Indah; Lady Pratiwi, Theodesia; Data, Aga; Badrah Zaki, Leil (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
The 21st-century educational landscape, shaped by technology and diverse student needs, emphasizes digital literacy, personalized learning, and innovative teaching. TikTok's role in enhancing English skills has been explored, showing positive impacts on proficiency and pronunciation. This study investigates TikTok's influence on English learning motivation among students, using a mixed-method approach at SMK Negeri 2 Batam. Classroom observations, questionnaires, and interviews with students and teachers form the data collection methods. Analysis involves defining objectives, data cleaning, selecting appropriate techniques, and drawing conclusions. The study aims to provide insights into leveraging technology for language learning, emphasizing the need for adaptable education to meet contemporary learners' demands.